2018
DOI: 10.1186/s12969-018-0239-8
|View full text |Cite
|
Sign up to set email alerts
|

Final adult height of patients with childhood-onset systemic lupus erythematosus: a cross sectional analysis

Abstract: BackgroundTo compare final height to mid-parental target height among adults with childhood-onset systemic lupus erythematosus (cSLE) versus adult-onset SLE (aSLE), and to evaluate the impact of age at SLE onset on final height.MethodsData derived from the Lupus Outcomes Study, a longitudinal cohort of adults with SLE, was used for this cross-sectional analysis (N = 728). Participants aged 18–63 years with complete height data were included (N = 566) and were classified as cSLE if age at diagnosis was < 18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(29 reference statements)
3
10
0
Order By: Relevance
“…A cross‐sectional study of adults with childhood‐onset SLE demonstrated that patients with childhood‐onset SLE were, on average, 2.4 cm shorter than their target height. The 17 female patients diagnosed with childhood‐onset SLE between age 11 and 13 years had the greatest risk for reduced final height, compared to patients with adult‐onset disease; however, the authors of that study did not report on the relationship between age of diagnosis and menarchal status in individuals (11).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A cross‐sectional study of adults with childhood‐onset SLE demonstrated that patients with childhood‐onset SLE were, on average, 2.4 cm shorter than their target height. The 17 female patients diagnosed with childhood‐onset SLE between age 11 and 13 years had the greatest risk for reduced final height, compared to patients with adult‐onset disease; however, the authors of that study did not report on the relationship between age of diagnosis and menarchal status in individuals (11).…”
Section: Discussionmentioning
confidence: 98%
“…As a result, the timing of childhood‐onset SLE diagnosis may have significant impacts on linear growth and, subsequently, final adult height related to disease activity and medication side‐effects. Few studies have described the final height achieved in patients diagnosed with childhood‐onset SLE (10,11). No prior study has examined the relationship of menarchal status at childhood‐onset SLE diagnosis and final adult height.…”
Section: Introductionmentioning
confidence: 99%
“…The detrimental effect of supraphysiologic glucocorticoid treatment on childhood growth is well known and has been described in children treated with steroids for autoimmune conditions [ 37 ] or inflammatory conditions such as asthma [ 38 ]. Adult height in CAH has been an outcome of interest in clinical studies over the years because it reflects the effect of cumulative exposure to both androgens and glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Heshin-Bekenstein et al[ 17 ] have recently revealed the final heights of 72 jSLE patients who entered into adulthood. In that study, patients’ heights were 2.4 cm shorter than their target heights.…”
Section: Discussionmentioning
confidence: 99%